Micromechatronics : modeling, analysis, and design with MATLAB - Giurgiutiu, Victor; Lyshevski, Sergey Edward (Boca Raton, Fla. ; London : CRC Press, 2009)
Micromechatronics: Modeling, Analysis, and Design with MATLAB, Second Edition provides clear, comprehensive coverage of mechatronic and electromechanical systems. It applies cornerstone fundamentals to the design of electromechanical systems, covers emerging software and hardware, introduces the rigorous theory, examines the design of high-performance systems, and helps develop problem-solving skills. Along with more streamlined material, this edition adds many new sections to existing chapters.
Introduction to Mechatronic Systems -- Electromagnetic and Electromechanics Fundamental -- Electrostatic and Variable Reluctance Electromechanical Motion Devices -- Permanent-Magnet Direct-Current Motion Devices and Actuators -- Induction Machines -- Permanent-Magnet Synchronous Machines and Their Applications -- Electronics and Power Electronics Solutions in Mechatronic Systems -- Control and Optimization of Mechatronic Systems -- Electroactive and Magnetoactive Materials -- Induced-Strain Actuators -- Piezoelectric Wafer Active Sensors -- Microcontrollers for Sensing, Actuation, and Process Control -- Fundamentals of Microfabrication -- Index.
Includes bibliographical references and index.
1
Keywords: Mechatronics; Microelectromechanical systems